Role of Gender in Burn-Induced Heterotopic Ossification and Mesenchymal Cell Osteogenic Differentiation. Issue 6 (June 2015) - Ranganathan, Kavitha; Peterson, Jonathan; Agarwal, Shailesh; Oluwatobi, Eboda; Loder, Shawn; Forsberg, Jonathan A.; Davis, Thomas A.; Buchman, Steven R.; Wang, Stewart C.; Levi, Benjamin
<x xml:space="preserve">Abstract</x> Background: Heterotopic ossification most commonly occurs after burn injury, joint arthroplasty, and trauma. Male gender has been identified as a risk factor for the development of heterotopic ossification. It remains unclear why adult male patients are more predisposed to this pathologic condition than adult female patients. In this study, the authors use their validated tenotomy/burn model to explore differences in heterotopic ossification between male and female mice. Methods: The authors used their Achilles tenotomy and burn model to evaluate the osteogenic potential of mesenchymal stem cells of male and female injured and noninjured mice. Groups consisted of injured male (n = 3), injured female (n = 3), noninjured male (n = 3), and noninjured female (n = 3) mice. The osteogenic potential of cells harvested from each group was assessed through RNA and protein levels and quantified using micro–computed tomographic scan. Histomorphometry was used to verify micro–computed tomographic findings, and immunohistochemistry was used to assess osteogenic signaling at the site of heterotopic ossification. Results: Mesenchymal stem cells of male mice demonstrated greater osteogenic gene and protein expression than those of female mice (p < 0.05). Male mice in the burn group formed 35 percent more bone than female mice in the burn group. This bone formation correlated with increased pSmad and insulin-like growth factor 1 signaling at the heterotopic ossification site in male mice. Conclusions: The authors demonstrate that male mice form quantitatively more bone compared with female mice using their burn/tenotomy model. These findings can be explained at least in part by differences in bone morphogenetic protein and insulin-like growth factor 1 signaling.